Evaluation of medico-demographic deathsof population in Кrasnoyarsk region caused by renal cancer - R. A. Zukov; Yu. A. Dykhno; A. V. Shulmin; V. V. Kozlov (Сибирский онкологический журнал)
In the article the characteristic of medico-demographic deaths caused by renal cancer among the population of Krasnoyarsk region is given. There are results of research with use of modern approaches of losses of health definition. The evaluation of medico-demographic deaths caused by renal cancer among the population of Krasnoyarsk region for the period 2010–2012 with using DALY method was produced. The largest difference in values of the indicator DALY was observed between male and female population in 2011 by a factor of 4,7. The maximum gap in DALY indicator between male and female population was observed in the group of 55–59 years. More than half of DALY deaths among male involve working age